THE THEORETICAL ASPECTS OF NATIONAL ECONOMY DEVELOPMENT IN THE CONDITIONS OF DIGITAL TRANSFORNATION - Yakushko, I.V. (The actual problems of regional economy development, 2022)
The development of the national economy in most developed countries today is taking place in difficult conditions of the digitalization of all spheres of society. In the economic sphere, the use of digital technologies is very active, as the potential of such technologies to ensure effective development of various economic systems is enormous. A significant list of modern information and communication technologies, the possibility of their use in different conditions increase the interest of scientists to learn about the peculiarities of these technologies’ development, their positive impact on the national economy functioning. The purpose of the article is to deepen theoretical provisions of the digitalization of the national economy and specify the features of its development in digital transformation of society. It was found within the study that digitalization is already an integral part of the functioning of economic systems at different hierarchical levels. Its objective and comprehensive level today can be felt in all sectors and branches of the national economy. Within the article, much attention is paid to understanding the essence of such concepts of digitalization and digital transformation. It is established that the categorical space that has been formed today in this arear of research is already quite wide. However, the very concept of digitalization and digital transformation occupy a key space within this space. Accordingly, within the article, current scientific approaches to these categories, which analysis allows to state that digitalization is a gradual process of the impact of modern information and communication technologies on certain social processes, and systems that are a result of such influence receive new incentives for their own development and gradually disappear, are considered. Digital transformation – a set of changes that occur in social systems, including and within the national economy as a result of the impact of modern information and communication technologies. Within the article, the main consequences of the national economy digitalization are also determined.